“Chemyzone”: An Innovative E-Magazine for Chemistry and Chemical Literacy Education on Addictive Substances to Support Sustainable Development Goals (SDGs) Completed with Bibliometric Analysis - Salma Novianti Amanullah; Cucu Zenab Subarkah; Ferli Septi Irwansyah; Riri Aisyah (Bumi Publikasi Nusantara, 2026)
Chemical literacy plays a vital role in enabling students to understand chemical concepts and their relevance to everyday life, particularly in addressing social challenges such as substance abuse. In Indonesia, the increasing prevalence of narcotics and psychotropic abuse among adolescents, coupled with limited engaging learning resources and a low national science literacy score, underscores the urgency for innovative educational media. This study introduces Chemyzone, a digital e-magazine designed to enhance chemical literacy on addictive substances. The study focused on the development phase to produce a visually engaging and accessible learning tool. We also added a bibliometric analysis to support this study. The resulting e-magazine integrates knowledge, context, competence, and attitude dimensions of chemical literacy, offering support for classroom instruction while extending its reach to the broader public. The findings suggest that Chemyzone has the potential to raise awareness and improve understanding of addictive substances through technology-based education. This study adds new information regarding sustainable development goals (SDGs).